Pengaruh Metode Latihan Acceleration Sprint terhadap Kemampuan Lari 60 Meter Siswa - Yulmardani Yulmardani (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
The problem in this study is the ability to run 60 meters Class V SDN 03 Pancung Tebal North Bayang District because 60 meters running are not in accordance with the time that should be achieved by junior-high-school students. Many factors cause the 60-meter running ability is not good, including the training method. For this reason, it is necessary to conduct a study with the aim to find out how much influence the acceleration sprint training method has on the ability to run 60 meters Class V SDN 03 Pancung Thick Bayang Utara District. This type of research is quasi-experimental. The study population was students of Class V SDN 03 Pancung Tebal District of North Bayang. Samples using purposive sampling technique, namely sampling based on the intentions that have been determined previously or with certain considerations, amounting to 15 people aged 11-13 years. Data was collected using a 60-meter student test with a 60-meter running ability test. The data analysis technique is the T-Test. The results of the data analysis show that: There is a significant influence on the acceleration sprint exercise of the ability to run 60 m Grade V students of SDN 03 Pancung Tebal, North Bayang District.